2020
DOI: 10.3892/ol.2020.12009
|View full text |Cite
|
Sign up to set email alerts
|

DEPDC1B promotes migration and invasion in pancreatic ductal adenocarcinoma by activating the Akt/GSK3β/Snail pathway

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a highly lethal disease, which frequently presents with distant metastasis. Further understanding of the molecular mechanism of PDAC is helpful to uncover novel and effective therapeutic strategies. DEP domain containing 1B (DEPDC1B) is known to play a role in the carcinogenesis and metastasis of several common types of cancer; however, its biological function and molecular mechanism in PDAC progression remain unclear. In the present study, the expression levels of DE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…To evaluate the role of DEPDC1B in LIHC, we used various online tools to observe the expression of DEPDC1B in LIHC. As indicated in Figure 1 , the expression of DEPDC1B was higher in LIHC tissues than in normal tissues, and this is consistent with the results in non-small cell lung cancer, oral cancer, malignant melanoma ( Xu et al, 2019 ), bladder cancer ( Lai et al, 2020 ), glioblastoma, and pancreatic cancer ( Liu et al, 2020 ). Using qPCR assay, we confirmed the higher DEPDC1B mRNA expression levels in LIHC than that in the normal tissues ( Figure 7 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…To evaluate the role of DEPDC1B in LIHC, we used various online tools to observe the expression of DEPDC1B in LIHC. As indicated in Figure 1 , the expression of DEPDC1B was higher in LIHC tissues than in normal tissues, and this is consistent with the results in non-small cell lung cancer, oral cancer, malignant melanoma ( Xu et al, 2019 ), bladder cancer ( Lai et al, 2020 ), glioblastoma, and pancreatic cancer ( Liu et al, 2020 ). Using qPCR assay, we confirmed the higher DEPDC1B mRNA expression levels in LIHC than that in the normal tissues ( Figure 7 ).…”
Section: Discussionsupporting
confidence: 88%
“…As a protein accumulating during G2 phase, Marchesi et al have reported that the role of DEPDC1B in coordinating de-adhesion and cell-cycle progression at mitotic entry ( Marchesi et al, 2014 ). Furthermore, increasing evidence in recent years suggests that the overexpression of DEPDC1B is associated with tumor aggressiveness and poor prognosis in cancers, such as oral cancer ( Su et al, 2014 ), malignant melanoma ( Xu et al, 2019 ), glioblastoma ( Chen et al, 2020 ), non-small cell lung ( Yang et al, 2014 ), and pancreatic cancers ( Mishra et al, 2019 ; Liu et al, 2020 ). These findings strongly suggest that DEPDC1B could potentially contribute to tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Our TCGA analysis revealed that DEPDC1B mRNA level was elevated in cutaneous melanoma and was correlated with poor survival. Several previous studies demonstrated that DEPDC1B expression is abnormally upregulated in various cancer types, including pancreatic ductal adenocarcinoma, [ 16 ] bladder cancer, [ 17 ] prostate cancer, [ 15 ] hepatocellular cancer, [ 18 ] glioblastoma, [ 14 ] oral cancer, [ 11 ] and soft‐tissue sarcomas, [ 37 ] and is associated with poor prognosis, yet the mechanism underlying its dysregulation remains unclear. We found that DEPDC1B expression was positively regulated by an oncogenic driver SOX10, which is required for melanoma formation and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of DEPDC1B expression is frequently associated with oncogenesis and metastasis in different cancer types. [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ] For example, exogenous expression of DEPDC1B delays cell death and increases cell proliferation in breast cancer cells; [ 19 ] overexpression of DEPDC1B enhances migration and invasion of non‐small‐cell lung cancer cells through the activation of Wnt/ β ‐catenin signaling; [ 10 ] DEPDC1B promotes anchoring‐independent growth, migration, and invasion of oral cancer cells via the activation of Rac1‐ERK signaling axis; [ 11 ] it also regulates the migration and invasion of pancreatic cancer through the activation of the RAC1/PAK1‐LIMK1‐cofilin1 signaling pathway; [ 13 ] contributes to the migration and invasion of pancreatic ductal adenocarcinoma cells via the activation of Akt/GSK3 β /Snail pathway; [ 16 ] and is required for the development of glioblastoma [ 14 ] and bladder cancer. [ 17 ] Recent studies have shown that DEPDC1B also induces epithelial‐mesenchymal transition and promotes prostate cancer cell proliferation via Rac1‐PAK signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Western blotting procedures were described in our previous study ( 18 ). The primary antibodies used were MISP (1:1,000, cat.no.…”
Section: Methodsmentioning
confidence: 99%